Application of a falsification strategy to a musculoskeletal model of the lower limb and accuracy of the predicted hip contact force vector - Modenese,L; Gopalakrishnan,A; Phillips,ATM (Journal of Biomechanics, 2013)
In the literature, lower limb musculoskeletal models validated against in vivo measured hip contact forces (HCFs) exhibit a tendency to overestimate the HCFs magnitude and predict inaccurate components of the HCF vector in the transverse plane. In order to investigate this issue, a musculoskeletal model was forced to produce HCFs identical to those measured and the resulting joint equilibrium equations were studied through both a general approach and a static optimization framework. In the former case, the existence of solutions to the equilibrium equations was investigated and the effect of varying the intersegmental moments and the muscle tetanic stress assessed: for a value of 100 N/cm2 and moments calculated from an inverse dynamics analysis on average only 62% of analyzed frames were solvable for level walking and 70% for stair climbing. In the static optimization study, the model could reproduce the experimental HCFs but the recruited muscles were unable to simultaneously equilibrate the hip intersegmental moments without the contribution of reserve moment actuators. Without constraints imposed on the HCFs, the predicted HCF vectors presented maximum angle deviations up to 22° for level walking and 33° for stair climbing during the gait stance phase. The influence of the medio-lateral HCF component on the solvability of the equilibrium equations and the muscle recruitment alteration when the model was forced to produce the experimental HCFs suggest that a more accurate geometrical representation of the gluteal muscles is mandatory to improve predictions of the HCF vector yielded by the static optimization technique.